Nyalam Adat ba' Alam: Swidden Cultivation and Political-Ecological Dynamics among the Dayak Krio, West Kalimantan, Indonesia - Uswatun Khasanah Enggar Saptaningrum; Rafi Rendian Sulaksono (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This study examines the sustainability of swidden cultivation among the Dayak Krio community living around the Krio River in Hulu Sungai Subdistrict, Ketapang Regency, West Kalimantan Province, within a political ecology framework. The problem formulation centers on how practices that are often stigmatized by the state and companies as